Implementasi Literasi Digital Pada Anak Usia 5–6 Tahun: Sebuah Kajian Literatur Sistematis - Devika Puspa Andriani; Noviana Mustapa (PAUDIA: Jurnal Penelitian dalam Bidang Pendidikan Anak Usia Dini, 2026)
This study aims to systematically synthesize the implementation of digital literacy in children aged 5–6 years. A Systematic Literature Review (SLR) was conducted using the PRISMA approach on articles published between 2015 and 2025 from Scopus, ScienceDirect, and complementary scholarly sources. Twenty studies met the inclusion criteria and were analyzed through data extraction, quality appraisal, and thematic synthesis. The synthesis produced three main themes: (1) the dominance of interactive and play-based digital media, such as tablets, digital storytelling, educational robots, and digital manipulatives; (2) the importance of an adult-mediated ecosystem involving teachers, parents, institutions, and learning contexts; and (3) persistent barriers related to access gaps, teacher competence, safe content, and policy fragmentation. The main contribution of this review is an integrative mapping of digital literacy implementation as an ecosystem that links technology, pedagogy, family support, and policy, rather than viewing digital literacy merely as children's ability to operate devices. These findings offer practical implications for early childhood teachers, parents, institutions, and policymakers in designing safe, developmentally appropriate, and sustainable digital literacy practices.